Spontaneous apoptosis of lymphocytes of ovary cancer patients - I. I. Antoneyeva; S. V. Boichuk (Бюллетень сибирской медицины, 2007)
Results of the study of the spontaneous apoptosis mechanisms of peripheral blood lymphocytes of ovary cancer (OC) patients are presented in the article. Dynamics of mitochondrial potential (MP) change, level of phosphatidylserine (PS) expression and DNA fragmentation were used as apoptosis markers. These parameters were estimated by flow cytometry. During the incubation process, DNA fragmentation in OC patient lymphocytes were more intensive and observed during earlier stages than those in donor lymphocytes. Also, reliable decrease of MP and increase of PS expression level were observed. The study results revealed increased reactivity of mitochondrial lymphocytes in OC patients and as a result, decreased resistance to spontaneous apoptosis processes.